Structure-activity relationships of rosiglitazone for peroxisome proliferator-activated receptor gamma transrepression. Issue 12 (15th June 2017) - Toyota, Yosuke; Nomura, Sayaka; Makishima, Makoto; Hashimoto, Yuichi; Ishikawa, Minoru
Graphical abstract: Abstract: Anti-inflammatory effects of peroxisome proliferator-activated receptor gamma (PPRAγ) ligands are thought to be largely due to PPARγ-mediated transrepression. Thus, transrepression-selective PPARγ ligands without agonistic activity or with only partial agonistic activity should exhibit anti-inflammatory properties with reduced side effects. Here, we investigated the structure-activity relationships (SARs) of PPARγ agonist rosiglitazone, focusing on transrepression activity. Alkenic analogs showed slightly more potent transrepression with reduced efficacy of transactivating agonistic activity. Removal of the alkyl group on the nitrogen atom improved selectivity for transrepression over transactivation. Among the synthesized compounds, 3l exhibited stronger transrepressional activity (IC50 : 14 μM) and weaker agonistic efficacy (11%) than rosiglitazone or pioglitazone.